2009
DOI: 10.1002/ibd.20867
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the pediatric ulcerative colitis activity index (PUCAI)

Abstract: This study on real-life, prospectively obtained data confirms that the PUCAI is highly feasible by virtue of the noninvasiveness, valid, and responsive index. The PUCAI can be used as a primary outcome measure to reflect disease activity in pediatric UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
188
1
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 267 publications
(216 citation statements)
references
References 33 publications
6
188
1
10
Order By: Relevance
“…BMI was converted to BMI z-scores according to growth curves of the general Greek pediatric population. Disease activity was quantified using the Pediatric Crohn's Disease Activity Index (37) and Pediatric Ulcerative Colitis Activity Index (38). Both these indexes have been validated in pediatric populations with IBD, with higher values corresponding to higher disease activity.…”
Section: Methodsmentioning
confidence: 99%
“…BMI was converted to BMI z-scores according to growth curves of the general Greek pediatric population. Disease activity was quantified using the Pediatric Crohn's Disease Activity Index (37) and Pediatric Ulcerative Colitis Activity Index (38). Both these indexes have been validated in pediatric populations with IBD, with higher values corresponding to higher disease activity.…”
Section: Methodsmentioning
confidence: 99%
“…Even in a prospectively collected ''real-life'' registry cohort, the PCDAI was scored in only 48% of eligible visits compared with 98% for the Pediatric Ulcerative Colitis Activity Index (PUCAI), which requires no laboratory values. 6 A recent study has found that data to complete the PCDAI retrospectively were available in the charts of only 20% of 3643 clinical visits. 7 Second, although the height item undoubtedly is a very important marker of disease activity in children, it is relevant only to young children in the Tanner-growing stages (until stages 2-3) and its calculation over many months reduces short-term responsiveness and discriminant validity.…”
mentioning
confidence: 99%
“…These six variables are abdominal pain, rectal bleeding, stool consistency, nocturnal stools, number of stools each 24 hours and interruption to normal activities. The PUCAI correlates closely with other indicators, such as physician global assessment and endoscopic scores (Turner et al 2009). This validated score, which is simple and non-invasive, can now be used to assess disease activity and to monitor changes in activity following intervention.…”
Section: Inflammatory Markers and Disease Activity In Paediatric Ucmentioning
confidence: 87%